Growth charts for Marfan syndrome in the Netherlands and analysis of genotype–phenotype relationships. Issue 2 (15th November 2022) - Lauffer, Peter; Pals, Gerard; Zwinderman, Aeilko H.; Postema, Floor A. M.; Baars, Marieke J. H.; Dulfer, Eelco; Hilhorst‐Hofstee, Yvonne; Houweling, Arjan C.; Kempers, Marlies; Krapels, Ingrid P. C.; van de Laar, Ingrid M. B. H.; Loeys, Bart; et al.
Abstract: To optimize care for children with Marfan syndrome (MFS) in the Netherlands, Dutch MFS growth charts were constructed. Additionally, we aimed to investigate the effect of FBN1 variant type (haploinsufficiency [HI]/dominant negative [DN]) on growth, and compare MFS‐related height increase across populations. Height and weight data of individuals with MFS aged 0–21 years were retrospectively collected. Generalized Additive Models for Location, Scale and Shape (GAMLSS) was used for growth chart modeling. To investigate genotype–phenotype relationships, FBN1 variant type was included as an independent variable in height‐for‐age and BMI‐for‐age models. MFS‐related height increase was compared with that of previous MFS growth studies from the United States, Korea, and France. Height and weight data of 389 individuals with MFS were included (210 males). Height‐for‐age, BMI‐for‐age, and weight‐for‐height charts reflected the tall and slender MFS habitus throughout childhood. Mean increase in height of individuals with MFS compared with the general Dutch population was significantly lower than in the other three MFS populations compared to their reference populations. FBN1‐ HI variants were associated with taller height in both sexes, and decreased BMI in females ( p ‐values <0.05). This Dutch MFS growth study broadens the notion that genetic background and MFS variant type (HI/DN) influence tall and slender stature in MFS.